(untitled) (Web of Teachers: Inderscience Research, 2024)
The economic competence of leaders within preschool education organizations is pivotal for the efficient management and sustainability of early childhood education institutions. This paper explores strategies to enhance the economic competence of preschool education organization leaders through professional development programs. Key strategies include financial management workshops focusing on budgeting, resource allocation, and financial planning tailored to the specific needs of preschool education organizations. Additionally, leaders should be educated on understanding various funding sources, cost management, revenue generation, and data analysis skills. Legal and regulatory compliance, strategic planning, and networking opportunities are also essential components of professional development programs aimed at enhancing economic competence. By implementing these strategies, preschool education organization leaders can build the necessary economic competence to ensure the financial sustainability and success of their institutions.